Ultrasonic Detection of Transversal Cracks in Rail Heads – Theoretical Approach - Tomasz KATZ; Sławomir MACKIEWICZ; Zbigniew RANACHOWSKI; Zbigniew L. KOWALEWSKI; Łukasz ANTOLIK (Engineering Transactions, 2021)
In the paper the calculation of ultrasonic field generated by the transmitting transducer and the pulse-echo amplitude received after beam reflection at the defect in tested material is presented. The focus of the authors is directed on the specific transducer – defect configurations where the common methods of determination of ultrasonic beam trajectory fails. The developed analytical model is based on well-established principles of elastodynamic theory and forms the basis for computer program for simulation of ultrasonic examination of railway rails.